Cultures of Empire, Nation, and Universe in Pres. José P. Laurel’s Political Thought, 1927–1949 - CuUnjieng, Nicole; Yale (Archīum Ateneo, 2017)
In order to refigure the period of Japanese occupation along a longerhistorical narrative of Filipino resistance to foreign domination, thisarticleexamines the mobilization and definition of the Filipino nation vis-à-visWestern imperialism and empire in the political thought of the wartimePhilippine president and Japanese “collaborator” José P. Laurel. In orderto elucidate the historical genealogies and legacies of empire informing histhought, thisarticle reconstructs and interrogates his universalism againsthis nationalism and his construction of Pan-Asianism and the Orient againstthat of Western imperialism and the Occident.Keywords: Pan-asianism • LaureL • imPeriaLism • nationaLism •universaLism